The Effectiveness of GEEKY KIA (Online Talking on Mom and Child Health) on the Anxiety Level of Pregnant Mothers in Facing the Delivery Process: Efektifitas CULUN KIA (Curhat Online Kesehatan Ibu dan Anak) terhadap Tingkat Kecemasan Ibu Hamil dalam Menghadapi Proses Persalinan pada Era New Normal - Prajayanti , Hilda; Maslikhah; Baroroh, Ida (Jurnal Kebidanan Midwiferia, 2022)
The Covid-19 pandemic is still engulfing all corners of the world, including Indonesia. To prevent the transmission of Covid-19, the government issued various appeals for stricter prevention such as Work from Home (WFH), the 3M program and the community was asked to stay at home, avoiding crowds. With conditions like this, people cannot carry out refreshing activities outside the home which causes people to have a higher level of saturation. Staying at home also has an impact on increasing pregnancy rates in fertile women. During this pregnancy, women are still required to make antenatal care visits to health care facilities by making an agreement with health workers so that delivery goes smoothly, mother and baby are healthy. With pandemic conditions like this, pregnant women, especially entering the third trimester, will increase the level of anxiety facing childbirth, especially pregnant women who want to give birth in the hospital. The policy at the hospital also requires that there is only 1 patient waiting. One way to reduce anxiety levels, we present CULUN KIA, which is a media designed to provide information related to the health of pregnant women and as an educational medium for pregnant women who are approaching labor which is intended to share information related to pregnancy, childbirth, babies and the postpartum period in